THE CORE ETHOS AND THE PROGRESSIVE SPIRIT OF MUHAMMADIYAH SOCIO-RELIGIOUS MOVEMENT - Baidhawy, Zakiyuddin; Khoiruddin, Azaki (Journal of Al-Tamaddun, 2018)
Beyond a century, Muhammadiyah, one of the largest socio-religious movements in Indonesia, remains continuously to uphold the ideals of establishing "the truly Islamic society". What is the Muhammadiyah spirit in facing the challenges of the times and spaces? Using library approach, this study argues that the Muhammadiyah always dedicated to and take inspiration from the three ethoses of the Quran in achieving the goal of building a truly Islamic society, those are the ethos of rahmah, al-Ma’un and al-â€˜Ashr that founded on integrative approach between the Quranic interpretation, the sacred heart-mind and the science-technology, and the universal human experience. Rahmah (compassion) is a key of developing the sacred heart-mind capabilities of how to save the lives of people in the world. Muhammadiyah, which is identical with the ethos of al-Ma`un (social praxis), tends to throwaway religious formalities for it has been included in the social orientation to advocate dhuâ€˜afa and mustadhâ€˜afin. Al-â€˜Ashr ethos defines religion (iman) and civilization (`amal shalih) two separated entities but in the state of collaboration. Through this way, Muhammadiyah is no longer exaggeratedly concerned with the issue of poverty and impoverishment, but also regarded to the effective systems, institutions, and leadership in building the perfect civilization.